2010
DOI: 10.1007/978-3-642-17373-8_7
|View full text |Cite
|
Sign up to set email alerts
|

The World Is Not Enough: Another Look on Second-Order DPA

Abstract: Abstract. In a recent work, Mangard et al. showed that under certain assumptions, the (so-called) standard univariate side-channel attacks using a distance-of-means test, correlation analysis and Gaussian templates are essentially equivalent. In this paper, we show that in the context of multivariate attacks against masked implementations, this conclusion does not hold anymore. While a single distinguisher can be used to compare the susceptibility of different unprotected devices to first-order DPA, understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 22 publications
6
102
1
Order By: Relevance
“…But they do not exhibit strongly different efficiencies. Overall, these experiments also follow the analysis in [30], which shows that the efficiency of non-profiled (second-order) side-channel distinguishers is difficult to predict and highly dependent on the implementation context.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…But they do not exhibit strongly different efficiencies. Overall, these experiments also follow the analysis in [30], which shows that the efficiency of non-profiled (second-order) side-channel distinguishers is difficult to predict and highly dependent on the implementation context.…”
Section: Methodssupporting
confidence: 69%
“…For example, [19,20,33] discuss the statistical properties of the original distinguisher; [9,20,22,30] consider its application to implementations protected by masking or other countermeasures; and [29] performs exhaustive empirical comparisons of various side-channel distinguishers, including MIA. In this paper, we compile these recent results into a single comprehensive treatment.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, our study relies on a well studied problem which is the comparison of the results of two different instantaneous attacks [11,20,33,34,36,38]. For the LRA, it will lead to a modification of the candidate selection rule.…”
Section: Effectiveness Discussionmentioning
confidence: 99%
“…In order to answer this question, we first repeated exactly the information theoretic analysis described in [30] and applied to the masking countermeasure in [31]. It leads to the information theoretic curves for the unprotected S-box and the 1st-order masked one in Figure 7.…”
Section: How Good Must the Randomness Be?mentioning
confidence: 99%
“…case of single-bit DPA attacks [3], then experimented by Standaert et al in more general contexts [31], and recently shown formally by Prouff and Rivain [25], using the mutual information put forward in [30] as evaluation metric.…”
mentioning
confidence: 99%